The effects of teacher expectations on student motivation to learn - Dragojević, Tamara; Letić Lungulov, Milena (Norma, 2022)
Starting from the understandings that emphasize the importance of the Pygmalion effect in teaching, the paper presents an overview of research on the relationship between teachers’ expectations and students’ motivation to learn. The aim of this paper is to point out the different effects of expectations that teachers form on students’ motivation to learn. The findings of the presented relevant research indicate that high expectations of teachers can increase student motivation, but also that low expectations of teachers can lead to its reduction. Also, it was determined that teachers smile more often, communicate more, establish eye contact with students from whom they expect more. The labels that teachers assign to students lead to some students getting less motivating learning situations. The implications of this paper are reflected in the elucidation of the significance of this phenomenon and its reflection on educational practice. It has been found that high as well as low expectations of teachers largely reflect on the motivation of students to learn, which is why teachers should use their influence by encouraging and activating students.